Effect of Audio Visual Instructional Media on Students’ Interest and Achievement in Algebra in Katsina Metropolis of Katsina State - Olaoye, A. E; Lawal Ashiru; UMAR, Sabiu (Journal of Higher Education and Academic Advancement, 2024)
This work examined effect of Audio Visual Instructional Media on secondary school students’ interest and achievement in Algebra in Katsina metropolis of Katsina state. The research adopted the non-equivalence, non-randomized control group quasi experimental design. Data were collected from a sample of 218 students comprising 117 boys and 101 girls from two randomly selected public Senor secondary schools in Katsina metropolis. Two research instruments, Algebraic Interest Questionnaire (AIQ) and Algebraic Achievement Test (AAT) and were used to gather data. The AIQ was a questionnaire consisting 15 items for the sampled pupils to tick as deemed appropriate to them while AAT was a researcher made instrument consisting of 25 items based on senior secondary school II scheme of work for four weeks. The items were objectives questions scored over 100 (4). The reliability coefficients of AIQ and AAT were 0.79 and 0.86 respectively. Data collected were analyzed using descriptive statistics of mean and standard deviation for answering the research questions and t-test at coefficient alpha level of 0.05 for testing the hypotheses. Major findings of this study includes: there was significant difference between the mean interest scores of experimental group exposed to Audio-visual instructional media and their counterparts in the control group and there was no significant difference between the mean achievement scores of male and female students exposed to Audio-visual instructional media. Based on these findings it was recommended that Mathematics teachers should be encouraged to use audio visual instructional media to teach mathematics.